Recurrent Perihepatic Abscesses Arising from a Gastric Remnant Leak: Delayed Complication of a Revision Roux-en-Y Gastric Bypass - Aboubacar Kaba; Florence-Damilola Odufalu; Zarir Ahmed; Charlene Prather; Mustafa Nazzal (Case Reports in Surgery)
Roux-en-Y gastric bypass is a procedure commonly used for weight loss associated with improved outcomes and decreased complications when compared to some counterparts. The procedure involves restriction of the stomach that is achieved by creation of a gastric pouch and bypass of the duodenum and a portion of the jejunum to aid in restrictive and malabsorptive weight loss. While many complications, both early and late, have been described following the procedure, recurrent perihepatic abscess has not been described in the literature. We present a case of a 66-year-old woman with recurrent extrahepatic abscesses following revision of a Roux-en-Y gastric bypass.